COMPARISON ON THE OCCURRENCES OF THE GENUS MAPANIA AUBLET (CYPERACEAE) FROM THE HEART OF BORNEO (HoB) - Zinnirah, Shabdin; Kalu, Meekiong (Forest Department Sarawak, 2020)
A comparison on the occurrences of the genus Mapania, family Cyperaceae from four selected areas of the Heart of Borneo (HoB) Project; namely Lanjak Entimau Wildlife Sanctuary (LEWS), Ulu Mentawai, Mulu National Park (UMMNP), Ulu Baleh National Park (UBNP) and Long Banga, Ulu Baram, Miri were conducted from the year 2008 until 2016. A total of 29 taxa representing by 24 species and 3 in-determined species were collected and identified from the four selected areas. The number recorded was considered high with 58.5% of the total number recorded for Sarawak. Only three taxa, viz. M. cuspidata var. cuspidata, M. meditensis and M. palustris were recorded occurred in all four selected sites. Whilst, M. sapuniana, M. ballehensis, M. kipas and M. mirae were identified as hyper-endemic; M. sapuniana from LEWS and the following three were from UBNP.